Mathematical Analysis on Catfish Production Dynamics In Rizal Laurence C. Gumpal... et al... - Laurence C. Gumpal; John Gabriel A. Amador; Eugene L. Aquino; Emmanuelle A. Cerdena; Jallen James F. Julian; Ariston, Ricardo R. (2024)
Catfish farming in Rizal, Philippines, is an important part of the local economy and helps ensure food security. This study uses a time series analysis model to look at the trends and seasonal indices to see the growth and production happens by months. By analyzing the data that has been collected, it allows us to see the flow and trend of the production for the last three years. The study uses Time Series Model to see how the pattern changes overtime and allows it to project the possible trend for the next year. According to the computation, the production rate has significantly slowed. The researchers use this model to see the data's trend, particularly the peak production. These results show how factors like demand, competitors, and other factors that the researchers haven't considered have a significant impact on catfish production. This synopsis demonstrates how time series models can provide valuable insights that startup entrepreneurs can utilize to comprehend the patterns and trends of catfish production in Rizal. Keywords: Catfish Production, Prediction, Time Series Model, Seasonal Index
Thesis